2021
DOI: 10.1088/1402-4896/ac2544
|View full text |Cite
|
Sign up to set email alerts
|

First principles study of perpendicular magnetic anisotropy in thin-film Co2MnSi

Abstract: Among different physical parameters taken into account for practical implementations in the field of spin-based electronics (spintronics), magnetocrystalline anisotropy (MCA) and spin polarization play a particularly important role. The former determines the orientation of magnetization direction, while a high degree of the latter is required for producing a spin-polarized current, a cornerstone of spintronics. Due to the miniaturization of the modern electronic devices, one often needs to consider physical ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The main features of the magneto-structural properties of Co 2 MnSi glass-coated microwires comes from the fabrication process where Co 2 MnSi Heusler compounds prepared with different form and technique (thin films, bulk and ribbons) does not show similar magneto-structural behavior at the same conditions [11][12][13][14][15][16]. As we described above, the main peculiarity of the Taylor-Ulitovsky method for preparing Heusler-alloy-based glass-coated microwires is the simultaneous rapid solidification of the metallic nucleus surrounded by the glass coating [24,27,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main features of the magneto-structural properties of Co 2 MnSi glass-coated microwires comes from the fabrication process where Co 2 MnSi Heusler compounds prepared with different form and technique (thin films, bulk and ribbons) does not show similar magneto-structural behavior at the same conditions [11][12][13][14][15][16]. As we described above, the main peculiarity of the Taylor-Ulitovsky method for preparing Heusler-alloy-based glass-coated microwires is the simultaneous rapid solidification of the metallic nucleus surrounded by the glass coating [24,27,47].…”
Section: Discussionmentioning
confidence: 99%
“…Among Heusler alloys based on 3d transition elements (especially, Co), Co 2 MnSi is of particular interest for advanced spintronic devices because of its large bandgap for minority spins (0.5 to 0.8 eV), high Curie temperature (~985 K), high tunnel magnetoresistance, large magnetoresistance ratios and perpendicular magnetic anisotropy [11][12][13][14]. Both the experimental and theoretical investigation conducted on Co 2 MnSi over the last two decades have been focused on the structural and magnetic properties and their relation to spin polarization [11,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Munira et al reported that Co 2 MnSi/MgO films have perpendicular anisotropy, which is related to Mn-O bonding near the Heusler alloy layer/MgO interface [16] and has been proven by experiment [17]. Later, the termination surface and mechanical strain on the PMA in free-standing thin-film Co 2 MnSi were investigated by firstprinciples study [18]. Despite these studies, there has been little investigation on the voltage and strain effects on the MA of Co 2 MnSi.…”
Section: Introductionmentioning
confidence: 94%
“…As a result, Co-based Heusler compounds are gaining the interest of the scientific community, and extensive studies and investigations have been carried out. Co 2 MnSi is a strong option for an advanced spintronic device, because of its high band gap for minority spins (0.5 to 0.8 eV), high Curie temperature (985 K), high tunnel magnetoresistance, large magnetoresistance ratios, and perpendicular magnetic anisotropy [17][18][19][20]. In the last two decades, both experimental and theoretical research on Co 2 MnSi have concentrated on the examination of its structural and magnetic characteristics and on their relationship to spin polarization [21][22][23].…”
Section: Introductionmentioning
confidence: 99%